Analysis Level of Interest in The Last Planner System (LPS) and Factors Influencing The Level of its Implementation - Muhammad Amin Rais; Imam Alfianto; Apif Miptahul Hajji (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the factors influencing the difficulty of implementing the Last Planner System (LPS) among contractors in Malang City. A quantitative approach was employed through questionnaires distributed to contractors involved in construction projects, supported by interviews to validate field findings. The data were analyzed using descriptive techniques and factor weighting to identify the variables that most significantly affect the challenges of LPS implementation. The results indicate that four major factors contribute to the level of difficulty in applying LPS: limited understanding and competence of human resources, lack of management support and commitment, weak coordination and communication among project teams, and resistance to organizational cultural change. The most influential factors are managerial and organizational behavioral aspects, particularly related to management commitment and readiness for collaborative work culture. These findings confirm that successful LPS implementation relies not only on technical tools but also on organizational readiness to adopt a culture of collaboration, transparency, and accountability. The study recommends strengthening human resource capacity, enhancing managerial support, optimizing routine coordination, and transforming organizational culture to improve the effectiveness of LPS implementation in Malang City.